(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
The dynamic development of Minsk, especially in the last decade, causes a constant intensive increase in the number and variety of vehicles, as well as an increase in the requirements of enterprises and citizens for the quality of transport services. There is an obvious need for further development and integration of such systems in order to transform them into an integrated system, i.e. a modern intelligent transport system that provides not only traffic monitoring and centralized adjustment of traffic light objects, but also automated optimal traffic control and automatic control. The installation of automatic fixation cameras is one of the methods used to control compliance with the speed limit (instantaneous speed). The development of optimal solutions for application should be based on the study of the operating experience of already existing devices in conditions as close as possible to real ones (pilot zones of trial operation) and be carried out taking into account the specifics of the tactical, technical and economic characteristics of the means of detecting and photo-video recording of traffic violations that are currently available on the world market. For this, a pilot project should be developed aimed at experimental testing of technology and means of fixing speed violations. Tasks implemented in the course of the pilot project: verification of the technology of recognition of state registration plates of vehicles and compliance with the round-the-clock operating mode (without supervision) "RoadEye S01"; formation of a model of the evidence base for an administrative offense; checking for compliance of the devices used with the requirements of manufacturability, compatibility, reliability, etc .; formation of general requirements for the organization of control zones for the average speed of movement, taking into account the results (statistics) for the pilot zone on the section of Olshevskogo street.